Experimental investigation of a R245fa-based organic Rankine cycle adapting two operation strategies: Stand alone and grid connect. (15th December 2017) - Feng, Yong-qiang; Hung, Tzu-Chen; Su, Ting-Ying; Wang, Shuang; Wang, Qian; Yang, Shih-Cheng; Lin, Jaw-Ren; Lin, Chih-Hung
Abstract: The operation characteristics of a 10 kW organic Rankine cycle using R245fa and adapting stand alone and grid connect operation strategies have been investigated. The heat input increases from 34.18 to 87.40 kW for stand alone and from 53.37 to 112.76 kW for grid connect operation strategy, while degree of superheating and subcooling are fixed at 9.5 ± 0.5 and 7 ± 0.5 °C, respectively. The detailed discussion for those four major components (pump, evaporator, expander and condenser) are examined, while the system overall performance is explored. The experimental results show that the expander rotating speed for stand alone operation strategy increases from 2320 to 2983 rpm, while that of grid connect operation strategy keeps constant of 3600 rpm with heat input. The stand alone operation strategy can run steadily at random operation zone, whereas the grid connect operation strategy is suitable for higher heat input. The maximum expander shaft power, electrical power and thermal efficiency are 7.16 kW, 6.32 kW and 4.89%, respectively. The maximum system generating efficiency for grid connect operation strategy is 4.59%, which is 35% higher than that of stand alone operation strategy approaching of 3.40%. Highlights: Operation characteristics of a 10 kW organic Rankine cycle using R245fa have been investigated. Two operation strategies (stand alone and grid connect) for ORC were examined. The stand alone operation strategy can run steadily at random operation zone. The maximum expander shaft power, electrical power and thermal efficiency are 7.16 kW, 6.32 kW and 4.89%, respectively.